Designing Active Learning Enriched Biotechnology Instruction Module (BIM) for Middle School Science Course - Serap Öz Aydın; Nursen Azizoğlu; Fatma Bilgican Yılmaz (Mimbar Sekolah Dasar, 2023)
This study aimed at designing instructional material named Biotechnology Instruction Module (BIM) which is enriched with active learning methods to enhance the 8th grade students’ learning of the topic. The development of the teaching materials proceeded within the stages of the ADDIE instructional design model. The final form of the instructional module comprised active learning materials of DNA Isolation Experiment, Bulletin Boards, 4x2 Biotechnology Learning Station, Case Studies Text, and “What Would You Do If You Were…?” activities. Instructional module covers the topics such as genetically modified organisms (GMO), gene therapy, cloning and bioremediation. The “Biotechnology Instruction Module” is expected to help students to learn in a meaningful way the rapidly changing and renewed biotechnology issues, to foster knowledge and understanding of key issues, to promote socioscientific discourse in class, and to encourage higher order thinking skills.  All the data show that the instructional module applied in the real classroom environment is successful in realizing the learning objectives of the subject of biotechnology.